The preferred chromatic composition of unfamiliar paintings is similar to original - Nascimento, Sérgio M. C. (2015)
The aim of this work was to compare the preferred chromatic composition for unfamiliar paintings with the original. Stimuli were images of paintings generated by rotating the color volume around the L* axis in CIELAB. The images were presented on a CRT. Four paintings were abstract from Amadeo de Souza-Cardoso, two had figurative elements from the same painter, two were abstract and two were figurative from other painters. In each trial a painting selected at random from the set was presented with its color volume rotated by angle selected at random. The task of the observer was to adjust the angle of the chromatic rotation for best subjective impression. Three groups of observers carried out the experiment: 50 without previous knowledge of the paintings, 8 experts in art but unfamiliar with the paintings tested and 6 experts in the paintings of Amadeo de Souza-Cardoso. It was found that the distribution of angles selected for data pooled across paintings for the non-specialist observers could be described by a Gaussian function centered at - 2 deg, i.e. close to the original colors of the paintings, and with a FWHM of 64 deg, just about 1.5 above the threshold to detect a chromatic change